The Organization of Political Parties and the Politics of Bureaucratic Reform - Cruz, Cesi; Keefer, Philip (World Bank, Washington, DC, 2014)
Bureaucratic reform is a priority of donor organizations, including the World Bank, but is notoriously difficult to implement. In many countries, politicians have little interest in the basic financial and personnel management systems that are essential to political oversight of bureaucratic performance. To explain this, this paper presents a new perspective on the political economy of bureaucracy. Politicians in some countries belong to parties that are organized to allow party members to act collectively to limit leader shirking. This is particularly the case with programmatic parties. Such politicians have stronger incentives to pursue public policies that require a well-functioning public administration. Novel evidence offers robust support for this argument. From a sample of 439 World Bank public sector reform loans in 109 countries, the paper finds that public sector reforms are more likely to succeed in countries with programmatic political parties.